الأفكار اللاعقلانية وعلاقتها بمفهوم الذات لدى المراهق المتمدرس - عيسو, عقيلة; بولحية, هاجر (جامعة الوادي - University of Eloued, 2022)
هدفت إلى التعرف على العلاقة بين الأفكار اللاعقلانية ومفهوم الذات لدى عينة من تلاميذ الطور الثانوي. تم استعمال المنهج الوصفي الارتباطي وتطبيق مقياسي الأفكار العقلانية واللاعقلانية لسليمان الريحاني (1985) وتنسي لمفهوم الذات، على عينة قدر عددها بـ 100 تلميذ وتلميذة، وبحساب معامل الارتباط بيرسون توصلنا إلى النتائج التالية: -توجد علاقة ارتباطيه عكسية دالة إحصائيا بين الأفكار اللاعقلانية ومفهوم الذات لدى عينة الدراسة، ما يعني أنه كلما ارتفعت الأفكار اللاعقلانية كلما انخفض مفهوم الذات؛ -لا توجد فروق دالة إحصائيا في الأفكار اللاعقلانية بين التلاميذ تعزى إلى متغير الجنس وأيضا الشعبة؛ -لا توجد فروق دالة إحصائيا في مفهوم الذات بين التلاميذ تعزى إلى متغير الجنس وكذا الشعبة An abstract is a brief, present study aimed to know the relationship between irrational ideas and self concept among gender secondary school, Where the descriptive correlation approach was used, and the researcher apply the scale of rational and irrational beliefs prepared by Rihani (1985), and the Tenisi scale as study instrument (1978) .on a sample of (100) people, after calculation of the correlation coefficient Pearson analysis of the results showed that: -There is a inverse correlation between irrational ideas and the notion of self in the study sample, which means that the higher the irrational ideas the lower the concept of self. -There are no differences based on the statistics in the irrational ideas of students due to the sex and specialty variable. -There are no differences based on the statistics in the self concept of students due to the sex and specialty variable.
مقال
Keywords: أفكار لا عقلانية ؛ ذات ؛ مفهوم ذات ؛ مراهقة; Irrational ideas; self; self concept; Adolescence